The Quality Test of Utilization of Palm Oil Solid Waste As a Raw Material For Refuse Derived Fuel (RDF) For Alternative Fuels. - Imam Gunadi, Gathut; Dahmir Dahlan (LPPM Politeknik Aceh Selatan, 2024)
The use of palm oil solid waste as a raw material for refuse derived fuel (RDF) is a promising alternative to overcome environmental and energy problems. This study aims to test the quality of RDF produced from palm solid waste by paying attention to the composition of the mixture and treatment method through quantitative experimental methods, which are divided into two stages: processing and quality testing. The results showed that the average calorific value of RDF reached 4,216.75 cal/g, moisture content 10.76%, ash content 4.37%, volatile matter 58.11%, and fixed carbon 26.75%, all of which showed great potential as an alternative energy source. Although the RDF calorific value of palm solid waste is higher than the industry standard, the moisture content and ash content are still below international standards, and the calorific value is slightly below the SNI class 1 standard but higher than that of class 2 and 3. These findings indicate that RDF from palm oil solid waste has the potential to be a good quality alternative fuel.